2013
DOI: 10.5812/jjm.7880
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotic Sensitivity of Bacteroid fragilis Isolated from Patients and Healthy Individuals in Imam Reza Center of Medical Teaching and Treatment-Tabriz

Abstract: Background:Bacteroides fragilis are among the most important anaerobic bacteria behind most of the anaerobic infections. They have acquired resistance to essential treatment antibiotics of anaerobic infections, more than other anaerobic bacteria. Objectives: The goal of this study is to determine the resistance of isolated B. fragilis against common anaerobic infections treatment antibiotics. Patients and Methods: A total of 188 fecal samples including 59 samples from hospitalized patients, 84 samples from out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…These results are similar to others study carried by Nakano et al ( 16 ). In contrast to the results obtained in our study, Akhi et al reported 5% resistance to metronidazole among B. fragilis isolates ( 7 ). In other previous studies, metronidazole resistant Bacteroides spp.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are similar to others study carried by Nakano et al ( 16 ). In contrast to the results obtained in our study, Akhi et al reported 5% resistance to metronidazole among B. fragilis isolates ( 7 ). In other previous studies, metronidazole resistant Bacteroides spp.…”
Section: Discussioncontrasting
confidence: 99%
“…Bacteroides fragilis is an anaerobic Gram-negative bacillus and a member of the normal flora community of the human gastrointestinal tract and vagina. B. fragilis represents a common cause of endogenous infections in humans that is frequently associated with polymicrobial infections such as intra-abdominal, diabetic foot, obstetric-gynecologic tract and surgical site infections, as well as toxin-dependent diarrhea in adults and children ( 7 , 8 ). Enterotoxigenic Bacteroides fragilis (ETBF) induced diarrhea in children has been reported by different researchers in various parts of the world, but ETBF has also been found in non-diarrheal fecal samples ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For enrichment and isolation of Clostridium perfringens , a drop of syringe specimen was introduced in cooked meat broth media and incubated at 45ºC for 4–6 h. Thereafter, one loop of this incubated media was sub-cultured in sheep blood agar plate and incubated under anaerobic condition and examined after 24 and 48 h [ 15 ], [ 17 ]. For identification of Gram-negative anaerobic bacteria, biochemical test such as reaction in Bile Esculin agar and MAST ID MID8 ANAEROB ID RING (MAST CO) was used [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The infections caused by anaerobic bacteria are some of the most important causes of morbidly and mortality in developing countries (Akhi et al, 2013). The development of resistance to metronidazole leading to treatment failure during the course of metronidazole therapy in a patient has been reported (Buta et al, 2010;Soki et al, 2013).…”
Section: Discussionmentioning
confidence: 99%